Multicriteria Spatial Data Analysis For Landslide Prone Zone in South Bogor Sub-District - Pamungkas, Prambudhianto Putro; Martono, Dwi Nowo; Soepaheluwakan, Jan (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
South Bogor District is one of the areas in Bogor City that has a high level of vulnerability to landslide disasters. Factors such as high rainfall, soil types that easily become saturated, steep slope inclinations, and land cover changes due to development are the main causes of the increased landslide risk. This research aims to map the landslide hazard levels in the area using a spatial approach with Geographic Information System (GIS) and a weighted overlay method. The five main parameters used in this analysis are slope gradient, soil type, rock type, land cover, and rainfall. Each parameter is weighted based on its contribution to the landslide potential. Data were obtained from various agencies such as BIG, BNPB, ESDM, and BPBD Kota Bogor. The overlay results show three hazard classes: low, medium, and high. Validation was carried out by comparing the zoning results with the actual landslide occurrence points recorded in the field. The research results show that most of the South Bogor District area falls into the moderate to high hazard class, especially in areas with steep slopes and non-forest land cover. Areas such as Kertamaya, Rancamaya, and Mulyaharja fall into high-risk zones, which aligns with previous landslide occurrence data. The resulting zoning model has proven capable of mapping potential hazards quite well and can serve as a basis for disaster mitigation planning, spatial planning, and landslide risk reduction policies in urban areas.